Experimental analysis of a double-slope solar still integrated with parabolic trough solar collector using nanofluid - Tugan, Volkan; Inalli, Mustafa; Isik, Erdem (Elsevier, 2025)
The use of solar energy in the treatment of saline water offers a sustainable and low-cost solution to the increasing global fresh water demand. In this direction, solar still systems separate water vapor from saline water by directly using solar radiation and then condense it to obtain pure water. However, their fresh water productivity is relatively low. Therefore, in this study, the fresh water productivity and thermal efficiency of the double slope solar distillation unit integrated with parabolic trough solar collector, which operates completely on solar energy, were investigated experimentally. In addition, the effect of water-based nanofluid containing multi-walled carbon nanotubes on the performance of the solar still was investigated. All the stills produced were compared in terms of fresh water productivity and thermal efficiency. According to the results obtained from the study, the highest daily productivity was found to be 1963.8 g/m2/day, 2008.5 g/m2/day, 2592.0 g/m2/day and 2937.6 g/m2/day for SSSS, DSSS, PTSC integrated DSSS and both NF and PTSC integrated DSSS, respectively. It was observed that the daily productivity of DSSS, DSSS with integrated PTSC, and DSSS with both PTSC and NF were 6.6 %, 42.2 %, and 49.6 % higher than SSSS, respectively. Additionally, it was observed that the thermal efficiency of DSSS using PTSC and NF was lower compared to SSSS due to its larger system area.
Keywords: Solar still; Parabolic trough solar collector; Nanofluid